2020
DOI: 10.1007/s10856-020-06370-0
|View full text |Cite
|
Sign up to set email alerts
|

Alginate films augmented with chlorhexidine hexametaphosphate particles provide sustained antimicrobial properties for application in wound care

Abstract: All chronic wounds are colonised by bacteria; for some, colonisation progresses to become infection. Alginate wound dressings are used for highly exuding chronic wounds as they are very absorbent, taking up large quantities of exudate while maintaining a moist wound bed to support healing. Some alginate dressings are doped with antimicrobials, most commonly silver, but evidence regarding the efficacy of these is largely inconclusive. This manuscript describes the development and in vitro assessment of alginate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The complex physiological process of wound healing, which includes highly coordinated hemostasis, inflammatory, proliferation, and maturation phases, is further complicated by wound infection, chronic diseases (diabetes, obesity, and cardiovascular complications), and poor care and patient lifestyle (smoking, drinking alcohol) [ 1 , 2 , 3 ]. Despite substantial progress in the discovery of healing agents, the healing of chronic wounds remains a key challenge for medical professionals [ 4 ]. Annually, more than 6.5 million patients suffer from chronic wounds in the United States, which has expanded the market of wound handling products to above 27 billion USD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complex physiological process of wound healing, which includes highly coordinated hemostasis, inflammatory, proliferation, and maturation phases, is further complicated by wound infection, chronic diseases (diabetes, obesity, and cardiovascular complications), and poor care and patient lifestyle (smoking, drinking alcohol) [ 1 , 2 , 3 ]. Despite substantial progress in the discovery of healing agents, the healing of chronic wounds remains a key challenge for medical professionals [ 4 ]. Annually, more than 6.5 million patients suffer from chronic wounds in the United States, which has expanded the market of wound handling products to above 27 billion USD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, honey could be combined with a silver-impregnated dressing to allow for controlled release of honey into the wound. This combination has not been reported for honey, however augmentation of silver-impregnated dressings with chlorhexidine has been demonstrated in vitro [ 40 ]. The potential remains for honey to be combined with antiseptics for topical therapeutic use.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some papers report about phase imaging to investigate alginate samples. Duckworth et al compared topography and phase images of alginate films with chlorhexidine hexametaphosphate particles as well as pure alginate films, as depicted in Figure 11 [ 169 ]. Opposite to Figure 10 , the authors here found a high roughness in both cases ( Figure 11 b,d), but only for the alginate film with chlorhexidine hexametaphosphate particles did they also find variations in stiffness, leading to variations in the phase image, while the phase image of the pure alginate film was quite even.…”
Section: Applicationsmentioning
confidence: 99%
“…Lateral image dimensions are 300 nm; the z -axis represents 40° (phase images) and 10 nm (topography), respectively. Reprinted from [ 169 ], originally published under a CC-BY license.…”
Section: Figurementioning
confidence: 99%